Clinical Manifestations and Complications of Children With COVID-19 Compared to Other Respiratory Viral Infections: A Cohort Inpatient Study From Rio de Janeiro, Brazil - Pucarelli-Lebreiro, Giuliana; Venceslau, Marianna Tavares; Cordeiro, Catherine Crespo; Maciel, Fernanda Queiroz; Anachoreta, Thiago Dias; Abreu, Thalita Fernandes de; Frota, Ana Cristina Cisne; Castiñeiras, Terezinha Marta Pereira Pinto; Costa, Analucia Mendes da; Lopes, Adriana Cristina da Luz; Campos, Ludmila Nascimento Rodrigues; Calvano, Luiza Maria; et al. (Frontiers in Pediatrics, 2022)
The COVID-19 clinical manifestations in children and adolescents with are diverse, despite the respiratory condition being the main presentation. Factors as comorbidities and other respiratory infections may play a role in the initial presentation of SARS-CoV-2 infection. This study aims to describe the epidemiological aspects, clinical and laboratory manifestations of pediatric patients admitted to a tertiary pediatric hospital in Rio de Janeiro, diagnosed with COVID-19, and compare these with other viral conditions during the first year of the SARS-CoV-2 pandemic. Methods - All patients under 18 years of age admitted with upper airway infection were enrolled and followed up for 30 days. The main dependent variable was laboratorial diagnosis of SARS-CoV-2, and independent variables were studied through logistic regression. Results- 533 patients were recruited, and 105 had confirmed SARS-CoV-2 infection. Detection of other viruses occurred in 34% of 264 tested participants. Six patients died (2 in SARS-COV-2 infected group). The variables independently associated with COVID-19 were older age (OR=1.1, 95%CI: 1.0 – 1.1), lower leukocytes count at entry (OR=0.9, 95% CI=0.8 – 0.9), and contact with suspected case (OR=1.6, 95%CI=1.0 – 2.6). Patients with COVID-19 presented higher odds to be admitted in an intensive care unit (OR=1.99, 95%CI=(1.08-3.66). Conclusions – Even during de SARS-COV2 pandemic, several other respiratory viruses were present in admitted pediatric patients. Variables associated with COVID19 infection were older age, lower leukocytes count at entry, and had a domiciliary suspect contact. Although patients with COVID-19 were more frequently admitted to ICU, we did not observed higher mortality in this group.